Drugs in pragnancy and lactation : a reference guide to fetal and neonatal risk - Briggs, Gerald G; Freeman, Roger K; Yaffe, Sumner J (Williams & Wilkins, 1998)
Univ. of California, San Francisco. Comprehensive reference for obstetric and pediatric clinicians on the use of drugs in pregnancy and lactation. Format lists drug name, class, risk factor, fetal risk summary, breast feeding summary, and key references. Previous edition: c1994. DNLM: Fetus--Effect of drugs on--Handbooks, manuals, etc.
Keywords: léčivé přípravky; plod; NOVOROZENCI; Fetus; kojení; gynekologie a porodnictví; Breast Feeding; farmacie a farmakologie; Pharmaceutical Preparations